Floating house on Tempe Lake in the regency of Wajo Indonesia - Armiwaty; Nurul Jamala; Baharuddin Hamsah; Rosady Mulyadi (2024)
This study aims to determine the development process of the formation of floating houses in Tempe Lake and the factors that influence it. The type of research is qualitative research whereby data is collected by means of field observation, interviews, and documentation. The data analysis techniques used are data collection, data presentation, data reduction, and conclusion drawing. The results showed that floating houses in Tempe Lake were formed as a result of the need for residential units that could bring residents closer to their workplaces. The factors that influence the formation process are the geographical conditions of Tempe Lake, climatic conditions, availability of local resources, social and economic aspects, technology, and traditional knowledge.